Surface Energy and Crystallite Size Comparisons by Applying Direct Current and Pulse Direct Current on Substrate Bias in PVD Process - Hashim, Hanizam; Md Nizam, Abd Rahman; Noraiham, Mohamad; Mohd Soufhwee, Abd Rahman (Trans Tech Publications, Switzerland, 2013)
Surface morphology homogeneity and energy modifications for in situ PVD process are two critical factors to prevent unexpected adhesion failure during machining or service. Unlike during film depositing, there is still much gap to be explored on applying pulsed biasing concepts to the substrate during in situ, to ensure the substrate surface readiness prior to film coating. The purpose of this paper is to study the effects of conventional direct current (DC) and pulse direct current (PDC) applied at substrate bias to the surface energy and crystallite size. Tungsten carbide (WC) cutting tool insert and titanium nitride (TiN) were used as substrate and hard coating respectively. The runs were conducted to compare the bias at DC (-500V) and PDC (-200V, -500V, -800V). The surface energy and crystallite size were characterized through wettability test and X-ray diffraction (XRD) analysis. The applying of PDC on the substrate bias was found to further enhance the characteristics of the surface compared to the conventional DC substrate bias.